2016
DOI: 10.1021/acsami.6b04529
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Growth of Crystalline Mn5O8 by Self-Limited Multilayer Deposition using Mn(EtCp)2 and O3

Abstract: This work investigates the use of ozone as a post-treatment of ALD-grown MnO and as a coreactant with bis(ethylcyclopentadienyl)manganese (Mn(EtCp)2) in ALD-like film growth. In situ quartz crystal microbalance measurements are used to monitor the mass changes during growth, which are coupled with ex situ materials characterization following deposition to evaluate the resulting film composition and structure. We determined that during O3 post-treatment of ALD-grown MnO, O3 oxidizes the near-surface region corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…[4][5]16 Among the different synthetic routes to manganese-based nanosystems, 6,17 chemical vapor deposition (CVD) and atomic layer deposition (ALD) hold a significant promise for the tailored fabrication of high quality films and nanoarchitectures. 1,[18][19][20] Nevertheless, the successful development of CVD/ALD synthetic protocols is directly dependent on the availability of volatile precursors, ensuring a reproducible mass supply and endowed with clean decomposition/fragmentation patterns. [21][22] So far, only a few reports on the preparation of MnF2 layers by ALD 23 and CVD 8 are present in the literature, whereas most studies have been dedicated to the synthesis of supported Mn oxide systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5]16 Among the different synthetic routes to manganese-based nanosystems, 6,17 chemical vapor deposition (CVD) and atomic layer deposition (ALD) hold a significant promise for the tailored fabrication of high quality films and nanoarchitectures. 1,[18][19][20] Nevertheless, the successful development of CVD/ALD synthetic protocols is directly dependent on the availability of volatile precursors, ensuring a reproducible mass supply and endowed with clean decomposition/fragmentation patterns. [21][22] So far, only a few reports on the preparation of MnF2 layers by ALD 23 and CVD 8 are present in the literature, whereas most studies have been dedicated to the synthesis of supported Mn oxide systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, several molecular precursors have been proposed and tested, encompassing different manganese bis(amidinates), 18,24 bis(ethylcyclopentadienyl)manganese 1,23,25-29 and various -diketonates, as, for instance, Mn(dpm)3 (Hdpm = 2,2,6,6-tetramethyl-3,5-heptanedione), [2][3]30 Mn(acac)2(H2O)2 (Hacac = 2,4pentanedione), 20 and Mn(hfa)2(H2O)2. 31 Some of these works have reported on the formation of Mn(II), 29 Mn(III) oxides, 2 Mn5O8, 1 as well as Mn3O4 3,32 and MnO2. 3 In most of these studies, the authors report on the formation of unspecified MnOx systems.…”
Section: Introductionmentioning
confidence: 99%
“…The phase dependence on ozone exposure can be used both to tune the phase between the pure γ phase and pure α phase and to control the orientation of crystalline domains. Other ALD processes relying on ozone as a coreactant may also exhibit similar behaviors, possibly including our preliminary work on NiO ALD and the study of MnO ALD by Young et al [ 70 ] Additionally, this mechanism may affect growth and behavior of ternary ALD systems by introducing reactive surface oxygen species that could influence the precursor chemisorption. Further investigation of these phenomena and more detailed mechanistic studies are the subject of future work.…”
Section: Resultsmentioning
confidence: 91%
“…Also similar to findings for NiO and Fe2O3, the authors reported an increase in oxygen content in MnOx corresponding to changes in oxide stoichiometry, high exposures needed to reach saturation, and film phase conversion. 55 On the contrary, deposition of aluminum oxide from trimethylaluminum and ozone does not seem to exhibit this behavior, instead saturating at a sub-monolayer GPC with much lower reactant exposures. 34,35 The presence of the oxygen reservoir phenomenon in some ozone-based, metal oxide ALD processes but not others raises the question of what chemical, material, and process properties are necessary to cause this subsurface reactive oxygen growth.…”
Section: Oxygen Reservoir Activation In Other Ald Processesmentioning
confidence: 99%